A CRISPR knockout screen identifies SETDB1-target retroelement silencing factors in embryonic stem cells - Fukuda, Kei; Okuda, Akihiko; Yusa, Kosuke; Shinkai, Yoichi (Genome Research, 2018)
In mouse embryonic stem cells (mESCs), the expression of provirus and endogenous retroelements is epigenetically repressed. Although many cellular factors involved in retroelement silencing have been identified, the complete molecular mechanism remains elusive. In this study, we performed a genome-wide CRISPR screen to advance our understanding of retroelement silencing in mESCs. The Moloney murine leukemia virus (MLV)–based retroviral vector MSCV-GFP, which is repressed by the SETDB1/TRIM28 pathway in mESCs, was used as a reporter provirus, and we identified more than 80 genes involved in this process. In particular, ATF7IP and the BAF complex components are linked with the repression of most of the SETDB1 targets. We characterized two factors, MORC2A and RESF1, of which RESF1 is a novel molecule in retroelement silencing. Although both factors are recruited to repress provirus, their roles in repression are different. MORC2A appears to function dependent on repressive epigenetic modifications, while RESF1 regulates repressive epigenetic modifications associated with SETDB1. Our genome-wide CRISPR screen cataloged genes which function at different levels in silencing of SETDB1-target retroelements and provides a useful resource for further molecular studies.